Anesthesia-free In-office Hysteroscopic Morcellation for Endometrial Polyps: A Prospective Study - Daiki Hiratsuka; Akira Tsuchiya; Akihisa Fujimoto; Osamu Nishii (Wolters Kluwer Medknow Publications, 2024)
Objectives: The objective of the study was to evaluate the feasibility and quality of anesthesia-free in-office hysteroscopic morcellation for the treatment of endometrial polyps. Materials and Methods: A prospective, single-center, open-label, single-arm clinical trial was conducted to evaluate the efficacy of hysteroscopic morcellation for endometrial polyps or retained products of conception. All surgical procedures were performed using the TruClear™ 5C system in the office setting without anesthesia. The primary endpoint was the success rate of surgery, defined as the completion of the operation. The secondary endpoints were operating time, fluid deficit, adverse events, pain evaluated by Visual Analog Scale (VAS) scores, and recurrence rate. Results: Ninety-five patients underwent hysteroscopic morcellation without anesthesia and received the treatment. The success rate of surgery was 100% (95/95), and the mean operating time was 7.3 min. Adverse events occurred in only 2.1% (2/95), with vasovagal reflex. The mean VAS scores during the procedure ranged from 2.4 to 3.1, and the recurrence rate after 6 months was 2.1% (1/47), with a pregnancy rate of 33% (11/33). When comparing nulliparous and parous patients, the success rate and the operating time were equivalent, and the mean VAS scores during the procedure were both within tolerable levels but significantly higher in nulliparous patients (3.3-4.5 vs. 1.6-1.9, P < 0.001). Conclusion: This study demonstrated that anesthesia-free in-office hysteroscopic morcellation for endometrial polyps can be safely performed with feasible quality and only tolerable pain. This less-invasive procedure is expected to become more widespread in future.